Why Should Parents Be Involved In Education? A Review Of The Research Literature - Ilham Handika; Arif Widodo (Jurnal Mantik, 2022)
A good education will be difficult to be realized without the collaboration among all education components. One of the elements which significantly contribute to determine the quality of eduction is the role of parents. However, many parents have no active engagement in education process of children. The phenomenon occurred shows that the educational process is still only concerned in the school. Education is only considered as the responsibility of the teacher only. There are a few parents that do the feedback from the educational process in the school. For its implication, the quality of education is not as well as expected. This study aims to acknowledge the importance of parents’ involvement in improving the quality of education. This study employs literature method. The procedure of the research was conducted by analyzing various relevant literatures to answer the research question. The finding shows that the involvement of parents in education is essential, especially in the level of elementary school. There are some kinds of activity which can be done by parents to collaborate with school. The involvement of parents in education can be realized by supporting students’ activity in school, appreciating students’ learning achievement, supervising, providing good facilities, and giving intensive learning guidance to students outside the school environment